Informality and optimal public policy (2016)
This article tackles the feature of optimal public policy such as the level of enforcement and the supply of public goods in an economy characterized by a huge informal sector. We consider informality as the group of productive activities which, before hand, do not comply (totally or partially) with government regulations. The Government intervenes as a Stackelberg leader and has to decide how to allocate public expenditures, collected through the tax system, between the provision of a public good, which can only be used for formal activities, and enforcement effort, aimed at detecting informal firms that evade taxes. Taking the public policy as given, a representative family, owner of a representative firm, decides how to split a fix amount of labour supply between formal and informal activities. Our results show that the greater are the distortions in the process of tax collection, the larger is the size of the informal sector. Finally we derive the properties of the optimal public policy. In particular, we show that the shadow cost of public fund represent the rationale of enforcement spending. We also point out that the size of the tax distortion (e.g. the shadow cost of public funds) is inversely related to total income, the tax rate and the provision of the public good.